2007
DOI: 10.1088/0029-5515/47/10/s03
|View full text |Cite
|
Sign up to set email alerts
|

21st IAEA Fusion Energy Conference: summary of sessions EX/D, EX/S and EX/W

Abstract: An overview is given of recent experimental results in the areas of divertor and exhaust, stability and waves and fast particles presented at the 2006 IAEA Fusion Energy Conference. Important new findings are presented from fusion devices worldwide, with a strong focus towards the needs of the major next step fusion experiment ITER.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Similar results were also found when optimising the launch angle in JT-60U [29]. We note here that a narrower deposition profile is also predicted to be beneficial for sawtooth tailoring and first hints of this have recently been obtained on ASDEX Upgrade [33]. Another important point is that only helical current of the same helicity as the magnetic island has a stabilizing effect, so that current driven in the area of the island O-point is stabilizing while helical current around the X-point is predicted to have a destabilizing effect.…”
Section: Progress In Understanding the Physics Of Ntm Stabilization Bsupporting
confidence: 82%
“…Similar results were also found when optimising the launch angle in JT-60U [29]. We note here that a narrower deposition profile is also predicted to be beneficial for sawtooth tailoring and first hints of this have recently been obtained on ASDEX Upgrade [33]. Another important point is that only helical current of the same helicity as the magnetic island has a stabilizing effect, so that current driven in the area of the island O-point is stabilizing while helical current around the X-point is predicted to have a destabilizing effect.…”
Section: Progress In Understanding the Physics Of Ntm Stabilization Bsupporting
confidence: 82%
“…Simulations also predict that counter-ECCD close to but inside the q = 1 surface should stabilize sawteeth. This has been confirmed on ASDEX Upgrade [20,22] and perhaps on JT-60U. On ASDEX Upgrade, moving counter-ECCD further inside q = 1 leads to complete elimination of the sawtooth crashes; however, from the changed MHD signature, it can be concluded that the stabilizing mechanism is different than that due to off-axis co-ECCD.…”
Section: Sawtooth Controlmentioning
confidence: 77%